First record of Parmelia asiatica (Parmeliaceae, Ascomycota) in Europe - Urbanavichene, Irina N.; Urbanavichus, Gennadii P. (Nature Conservation Research: Заповедная наука, 2024)
The lichen Parmelia asiatica (Parmeliaceae), described in 2011 from China (Yunnan province), is reported for the first time in Europe, in European Russia. Since 2013, the species has been recorded in the Russian Far East and Baikal Siberia. The majority of the records are in Protected Areas located in regions with a humid climate, where the preferred habitats are mainly foothill/mountain, humid, mixed or dark coniferous old-growth forests. A critical analysis of the herbarium specimens from the Kerzhensky State Nature Reserve (Nizhny Novgorod Region, Russia) collected by the authors in 2020 allowed us to identify a specimen as Parmelia asiatica. Before this study, only six species of the genus Parmelia were known in European Russia. The present paper contains data on the new record of P. asiatica, its morphology, the species distribution range, and its ecology. The diversity of data collected in Russian state nature reserves (including the new record) proves the need and importance of studying the lichen flora of these territories, since they represent the best-preserved, rare and unique habitats. In particular, the Kerzhensky State Nature Reserve is believed to be located near the contact zone between European and Siberian vascular and lichen flora, which is also confirmed by the here reported record of P. asiatica.